(untitled) (Research, Society and Development, 2022)
The objective of this work was to analyze the effect of nitrogen application on the fruit quality components of "granada" watermelon. For this, an experiment was carried out at Farm Extrema, located in the municipality of Arinos, state of Minas Gerais, from September to December 2018. The experimental design was a completely randomized block with five treatments and four replications. The treatments consisted of five levels of nitrogen fertilization: 0, 40, 80, 160 and 320 kg ha-1 of N. Fruit analyzes were carried out at the Chemistry laboratory of the Federal Institute of Education, Science and Technology of Minas Gerais - Campus Arinos. Physicochemical tests were performed to determine total soluble solids (° Brix), pH, titratable acidity (TA) and shell thickness. Nitrogen fertilization had a significant effect on the analyzed variables, except the pH of the fruits. The highest soluble solids content (8.27 °Brix) was obtained at the level of 171.7 kg ha-1 of N. For TA and bark thickness, significant linear models were adjusted (p <0.01).